2000
DOI: 10.1161/01.cir.102.24.3015
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin-Induced Mortality Is Related to Increased Oxidative Stress and End-Organ Dysfunction, Not Refractory Hypotension, in Heme Oxygenase-1–Deficient Mice

Abstract: These data suggest that the increased mortality during endotoxemia in HO-1(-/-) mice is related to increased oxidative stress and end-organ (renal and hepatic) damage, not to refractory hypotension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(148 citation statements)
references
References 29 publications
4
143
1
Order By: Relevance
“…HO-1 and its metabolites have been shown to exhibit beneficial anti-inflammatory properties in pure inflammatory models of disease such as endotoxemia (38). However, inhibition of the inflammatory response to bacterial infection by the HO-1 system might disrupt the ability of the immune system to eliminate invading bacteria.…”
Section: Ho-1 Impairs Host Defense Of Macrophages Against B Pseudomamentioning
confidence: 99%
“…HO-1 and its metabolites have been shown to exhibit beneficial anti-inflammatory properties in pure inflammatory models of disease such as endotoxemia (38). However, inhibition of the inflammatory response to bacterial infection by the HO-1 system might disrupt the ability of the immune system to eliminate invading bacteria.…”
Section: Ho-1 Impairs Host Defense Of Macrophages Against B Pseudomamentioning
confidence: 99%
“…These animals display severe growth retardation, anemia, iron deposition in the kidneys and liver, and evidence of chronic inflammation in a variety of organs. In other investigations involving HO-1 null mutant mice the animals have been demonstrated to be more susceptible to: 1) renovascular-related hypertension, renal failure, and cardiac hypertrophy (102), 2) endotoxin-mediated lethality (103), and 3) right ventricular dilation and infarction secondary to chronic hypoxia (104). Collectively, the in vitro, in vivo, and gene deletion studies outlined above provide compelling evidence regarding the broad cytoprotective role of HO-1 in clinically relevant forms of cellular and tissue injury.…”
Section: Hsp 32 (Heme Oxygenase)mentioning
confidence: 99%
“…Wiesel et al 12 found that HO-1 knockout mice show increased end-organ damage and death. Pae et al 13 also reported that HO-1 has protective properties in allergic inflammation, and other researchers *The first two authors contributed equally to this work.…”
Section: Introduction Imentioning
confidence: 99%